Plasma focusing devices in external programmed magnetic field - Ivanov, B.I. (Вопросы атомной науки и техники, 1999)
At present there is a significant requirement for the development of devices for focusing high-energy intense ion beams for the solution of actual scientific and technological problems (inertial thermonuclear fusion on heavy and light ions, radiotherapy, high energy investigations, research of radiation resistance of materials, implantation metallurgy, etc.).